Benefits and Shortcomings of an Established Sexual Assault Response Team: A Qualitative Examination of Stakeholder Interviews - Koon-Magnin, Sarah (American journal of criminal justice, 2023)
In order to combat sexual violence and better respond to victims of sexual assault, some jurisdictions have taken steps, including the creation of Sexual Assault Response Teams (SARTs). SARTs are generally comprised of representatives from the agencies primarily tasked with responding to sexual assault within the jurisdiction (e.g., law enforcement, advocates, prosecutors, and sexual assault nurse examiners). Ten members of SART were interviewed about the benefits and shortcomings of the organization. Results indicated that all members believed that interdisciplinary collaboration and mutual respect were both imperative to a successful SART. Furthermore, members identified benefits to themselves individually, in their role on the team, to victims, and to SART as a whole. Finally, shortcomings of SART emerged.